Revenue Discretionary Model Pengukuran Manajemen Laba: Berdasarkan Sektor Industri Manufaktur di Bursa Efek Indonesia - Nieken Herma Sari; Nurmala Ahmar (Jurnal Akuntansi dan Keuangan, 2014)
Earnings management is a management action to manage the profitability of a company. The purpose of this study is to indicate the accrual earning management using revenue discretionary model. This study adopts the research conducted by Stubben (2010) where there are two measurement models to detect the presence of accrual earnings management. The measurement model is the discretionary revenue model consists of conditional revenue model and revenue model. Object of this research is the companies listed in Indonesia Stock Exchange. The technique of data analysis is descriptive statistics to determine the residual value in each industry sector. These results prove that the revenue model is able to indicate the industrial sector 8 of the total 13 industries in the manufacturing companies indicated accrual earnings management. Conditional revenue model is able to indicate the industrial sector 11 of the total 18 sectors industry that overall indicated accrual earnings management.